Estratégia de gerenciamento de uma microrrede isolada integrando geração fotovoltaica e armazenamento em hidrogênio verde - Dal Forno, Igor Luiz (2025)
The growing global concern about climate change and the need to decarbonize energy matrices have driven the transition to renewable sources and sustainable electricity generation solutions. In this context, microgrids have emerged as a promising alternative, especially for remote areas not connected to the conventional power grid, offering greater autonomy, resilience, and sustainability. This dissertation proposes an energy management strategy for an isolated microgrid composed of photovoltaic generation, a battery bank, an electrolyzer, a hydrogen storage tank, and a fuel cell. Its operational philosophy prioritizes the use of solar energy to supply loads. When there is excess photovoltaic generation, it is directed to hydrogen production via the electrolyzer. The energy stored in the form of hydrogen is converted back into electricity by the fuel cell only under critical conditions, such as nighttime or low irradiation periods, after the battery is depleted. This approach reduces the use of the fuel cell, maximizing system efficiency. To coordinate the microgrid’s operation, an Energy Management System (EMS) was developed, structured into two main modes: initialization and operation. In the initialization mode, the load remains disconnected, and the excess photovoltaic generation is used exclusively to produce the minimum amount of hydrogen required for the system’s safe startup. In the operation mode, the load is connected, and the EMS manages energy distribution, prioritizing the use of solar energy to meet demand while directing the surplus to hydrogen production. The EMS also incorporates two functional modules: the first is the Human-Machine Interface (HMI), which allows the operator to monitor the system in real-time, activate or deactivate the EMS, and manually force transitions between the two modes; the second is the contingency module, responsible for ensuring continued operation under abnormal conditions, such as equipment failures. To test the developed EMS, the microgrid components were modeled in the Typhoon HIL environment for real-time simulation. The EMS was implemented on an external computer, and communication with Typhoon HIL was carried out via the Modbus TCP/IP protocol. A supervisory system for real-time visualization and control of the system was also developed on this computer. The simulation results demonstrated that the proposed management strategy was effective in maintaining the microgrid operation according to the defined philosophy and was validated under different operational scenarios.